Pengaruh Kampanye Pendidikan Media pada Perilaku Anak dalam Menonton Televisi - Tandiyo Pradekso (Master of Communication Science Program, Universitas Diponegoro, 2014)
The research was aimed to assess a media literacy program for teachers and parents of Mangunharjo elementary school and measured its influence on their children’s television viewing behavior. Employing a quasi-experimental method, the result suggested that the campaign program did have some effects on the children’s television viewing behavior. The average decrease of viewing duration during the weekend or holiday (0,78 hour) was higher than the weekdays (0,25 hour). Yet, there were no median differences of total hours of watching television during weekdays between prior and post treatment, that was 3 hours. The median differences of total hours of watching television during weekend decreased to 2 hours from 2,5 hours. The mode of total hour of watching television during weekdays decreased to 2 hours from 3 hours, while during the weekend the mode was not watching television (0 hour) compared to 2 hours before the campaign.